How we love eaudiobook Discover your love style, enhance your marriage. - Verner, Adam (christianaudio, 2016)
Identify the source of missteps in your marriage-and learn exactly what you can do about it!Tired of arguing with your spouse over the same old issues? Longing for a marriage with less conflict and more intimacy? Struggling under a load of resentment?In How We Love, relationship experts Milan and Kay Yerkovich draw on the powerful tool of attachment theory to show how your early life experiences created an "intimacy imprint"-an underlying blueprint that shapes your behavior, beliefs, and expectations of all relationships, especially your marriage. They identify four types of injured imprints that combine in marriage to trap couples in a repetitive dance of pain. The groundbreaking principles and practical, solution-focused tools in this book will equip you to...·identify the imprints disrupting your marriage,·understand how your love style impacts your mate,·break free of negative patterns that hinder your relationship,·enhance your sexual intimacy, and·create the deeper, richer marriage of your dreams.Discover the truths that have transformed countless relationships- including the authors' marriage-so you can stop stepping on each other's toes and instead be swept along by the music of a richer, more passionate relationship.